New insights into CAR T-cell hematological toxicities: manifestations, mechanisms, and effective management strategies - Yuanyuan Yang; Hongwei Peng; Jianxiang Wang; Fei Li (Experimental Hematology & Oncology)
Abstract Chimeric antigen receptor (CAR) T-cell therapy represents a highly efficacious treatment modality demonstrated to enhance outcomes in patients afflicted with malignancies, particularly those enduring relapsed or refractory hematological malignancies. However, the escalating adoption of CAR T-cell therapy has unveiled several life-threatening toxicities, notably cytokine release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), infections, and hematological toxicities (HTs), thereby hindering the broad implementation of CAR T-cell therapy. HTs encompass a spectrum of adverse effects, including cytopenias, hemophagocytic lymphohistiocytosis (HLH), coagulopathies, and B-cell aplasia. While our comprehension of the underlying mechanisms governing CRS and ICANS is advancing, the intricate pathophysiology of HTs remains inadequately elucidated. Such knowledge gaps may precipitate suboptimal therapeutic decisions, potentially culminating in substantial medical resource depletion and detriment to patients’ quality of life. In this comprehensive review, based on recent updated findings, we delineate various mechanisms contributing to HTs subsequent to CAR T-cell therapy, explicate manifestations of HTs, and proffer strategic interventions to mitigate this relevant clinical challenge.